Interspecific comparison of Drosophila serendipity and : multimodular structure of these C[[2]]H[[2]] zinc finger proteins. - Ferrer, P.; Crozatier, M.; Salles, C.; Vincent, A. (Journal of Molecular Evolution, 1994)
The Drosophila serendipity (sry) beta and delta genes, which resulted from a gene duplication event, provide an interesting model for the evolutionary diversification in structure and function of C2H2 zinc finger proteins. We examined here the divergence of the sry beta and delta proteins over an estimated period of 45 million years by comparing their predicted sequences in D. melanogaster, D. pseudoobscura, and D. subobscura. Between orthologs, i.e., pairs of either sry beta or sry delta, the NH2-proximal region delineated by pairs of C-X2-C motifs and the DNA-binding finger domain are highly conserved. Sequence conservation operates over the entire finger domain, including the links separating adjacent fingers, even though each has a unique sequence different from the widespread TGEKP motif. In contrast, the sequence of the central acidic region has extensively diverged and differs between species in the number of amino acids, probably because of slippage-driven mutations. The NH2-terminal region and fingers 1, 5, and 6 differentiate the sry beta and delta proteins while zinc fingers 2, 3, and 4 are virtually identical in these two paralogs. A nuclear localization signal of the SV40T antigen type, preceded by a potential CKII phosphorylation regulatory site, is conserved in sry delta but not found in sry beta. The interspecific conserved regions correlate well with the positions of zygotic lethal mutations in the D. melanogaster sry delta protein. Furthermore, P-element transformation experiments show that a transgenic copy of the D. pseudoobscura sry delta gene rescues the sry delta mutant phenotype. Convergence of genetic and structural data on the sry proteins supports a multimodular function and mode of evolution of these C2H2 finger proteins.